Is surgical antibiotic prophylaxis necessary for pediatric orchiopexy?. Issue 3 (June 2018) - Rensing, A.J.; Whittam, B.M.; Chan, K.H.; Cain, M.P.; Carroll, A.E.; Bennett, W.E.
Summary: Introduction: Surgeons frequently use surgical antibiotic prophylaxis (SAP), despite limited evidence to support its efficacy. Potential adverse events associated with antibiotic use include allergic reaction (including anaphylaxis), Clostridium difficile infection, and selecting for resistant bacteria. Surgical site infections (SSI) are very rare in patients undergoing clean pediatric urologic procedures. Current guidelines are unclear about the efficacy of surgical antibiotic prophylaxis for prevention of SSI in the pediatric population. Objective: It was hypothesized that children who received SAP prior to orchiopexy would have no reduction in surgical site infection (SSI) risk but an increased risk of antibiotic-associated adverse events. Methods: A retrospective cohort study was conducted of all males aged between 30 days and 18 years who underwent an orchiopexy (ICD-9 CM 62.5) in an ambulatory or observation setting from 2004 to 2015 using the Pediatric Health Information System database. Inpatients and those with concomitant procedures were excluded. Chi-squared or Fisher's exact tests were used to determine the association between SAP and allergic reaction (defined as a charge for epinephrine or ICD-9 diagnosis code for allergic reaction on the date of surgery) and any of the following within 30 days: SSI, hospital readmission or any repeat hospital encounter. Mixed effects logistic regression was performed, controlling for age, race, and insurance, and clustering of similar practice patterns by hospital. Results: A total of 71, 767 patients were included: median age was 4.6 years, 61.4% were white, and 49.3% had public insurance; 33.5% received SAP. Of these participants, 996/71, 767 (1.4%) had a perioperative allergic reaction and <0.1% were diagnosed with an SSI. On mixed effects logistic regression, those who received SAP had 1.2 times the odds of a perioperative allergic reaction compared with those who did not receive SAP ( P = 0.005). Surgical antibiotic prophylaxis was not associated with decreased rates of SSI, lower hospital readmission, nor a lower chance of a repeat encounter within 30 days. Conclusions: In patients undergoing orchiopexy, it was found that SAP did not reduce the risk of postoperative SSI, readmissions, or hospital visits. Patients who received SAP had significantly increased odds of perioperative allergic reaction. This demonstrated that the risks of SAP outweigh the benefits in children undergoing orchiopexy.